Demonstration of Improved Banana (William-1 Variety) Production and Commercialization in Nyanghtom District of South Omo Zone, Southern Ethiopia - Eshbel, Atlaw; Adicha, Asmera; Tadesse, Anteneh; Tadesse, Awoke; Geberemeskel, Yibrah (Research on World Agricultural Economy, 2023)
A demonstration of improved banana production and commercialization was conducted in the Nyanghtom district of the South Omo Zone to enhance the livelihoods of pastoralists and agro-pastoralists in the area. One improved banana variety (Wiliyams-1) was used for the demonstration and planted on one hectare of land after training was given for purposively selected 25 trial pastoral agro-pastoral research and extension groups and 7 nontrial agro-pastorals from land preparation to harvesting. Relevant data through individual interviews and measurement of agronomic parameters were collected. The collected data were analyzed by descriptive statistics and Likert scale measurement of agro-pastoral preference. Based on the results, the mean banana fruit produced was 28.4 ton ha–1 under agro-pastoral management and also agro-pastoral preference indicated that the variety Wiliyam-1 was the first choice of agro pastorals in all parameters except drought resistance. Cost-benefit analysis results indicated that the average net income obtained from banana production was 209,647 Ethiopian Birr ha–1. The cost-benefit ratio of 2.95:1 indicated that the benefit of production was nearly three times higher than the cost of production. However, agro-pastoral raised the frequent breakdown of water pumps, lack of operation and maintenance skills, and the high cost of fuel to operate generators and tractors were major bottlenecks to sustaining production. Therefore, strong efforts of respective stakeholders are needed to resolve irrigation water access problems for sustainable banana production and commercialization to ensure food security and improve the livelihoods of women and agro-pastorals. ER